Conditional Capital Practice in Empagae Village, Wattang Sidenreng District, Sidenreng Rappang Regency (Islamic Economic Law Perspective) - Faradhillah, Nitha; Rusdi, M. Ali; Muliati (Program Studi Hukum Ekonomi Syariah, Institut Agama Islam Negeri Parepare, 2022)
The practice of conditional capital that occurs in Empagae Village is an economic activity that involves two parties, namely: the lender and the borrower. This conditional capital loan started from a borrower who needed capital to purchase seeds and farm fertilizers, who then borrowed a sum of money by offering conditions for the loan that had been given, namely